2022
DOI: 10.3390/biom12020221
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of Drosophila Melanogaster—A Nutritional Perspective

Abstract: The model organism Drosophila melanogaster was increasingly applied in nutrition research in recent years. A range of methods are available for the phenotyping of D. melanogaster, which are outlined in the first part of this review. The methods include determinations of body weight, body composition, food intake, lifespan, locomotor activity, reproductive capacity and stress tolerance. In the second part, the practical application of the phenotyping of flies is demonstrated via a discussion of obese phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 279 publications
(385 reference statements)
1
18
0
Order By: Relevance
“…Subsequently, the mRNA levels of genes involved in glucose and lipid metabolism significantly altered in flies with HSD consumption ( Supplementary Figure S5 ). Our results revealed that 30%HSD intake led to the pathophysiological and transcriptional changes in Drosophila , which are consistent with the T2DM phenotype as previously reported ( Meshrif et al, 2022 ) ( Eickelberg et al, 2022 ). In the present study, HSD participated the growth and development stages of Drosophila , therefore affecting the organ development and insulin action, which in turn influenced the glucose homeostasis and insulin sensitivity of flies ( Cassim et al, 2018 ).…”
Section: Resultssupporting
confidence: 92%
“…Subsequently, the mRNA levels of genes involved in glucose and lipid metabolism significantly altered in flies with HSD consumption ( Supplementary Figure S5 ). Our results revealed that 30%HSD intake led to the pathophysiological and transcriptional changes in Drosophila , which are consistent with the T2DM phenotype as previously reported ( Meshrif et al, 2022 ) ( Eickelberg et al, 2022 ). In the present study, HSD participated the growth and development stages of Drosophila , therefore affecting the organ development and insulin action, which in turn influenced the glucose homeostasis and insulin sensitivity of flies ( Cassim et al, 2018 ).…”
Section: Resultssupporting
confidence: 92%
“…A HFD not only induced obesity but also caused heart dysfunction, which was found to be regulated by the TOR pathway [ 57 , 58 ]. HSD and HFD treatments increase fat storage in flies and also affect carbohydrate-insulin homeostasis, lifespan, locomotor activity, and stress tolerance [ 59 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…Microarray analysis of adult flies on the different diets showed that only 2–3% of the ~18,000 genes were influenced by the diet [ 96 ]. Drosophila is therefore a valuable model in which to combine nutrigenomics with the analysis of longevity and metabolic diseases in relation to nutrition [ 59 , 96 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…By applying the model organism D. melanogaster , the short- and long-term effects of feeding a high-energy diet can be systematically examined [ 11 , 12 ]. The fruit fly is characterized by a high reproductive rate, a short life cycle and a relatively short lifespan of 60–80 days.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit fly is characterized by a high reproductive rate, a short life cycle and a relatively short lifespan of 60–80 days. Hence, the impact of dietary interventions on life-history traits, such as feeding, locomotor behavior, longevity, metabolism, reproductive capacity, and stress tolerance can be studied within a relatively short period of time and cost-effectively since sophisticated experimental equipment is often not required [ 12 ]. In addition, most of the core metabolic and signal transduction pathways are evolutionary highly conserved between D. melanogaster and mammals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%